1994
DOI: 10.2172/10126086
|View full text |Cite
|
Sign up to set email alerts
|

L-H confinement mode dynamics in three-dimensional state space

Abstract: DISCLAIMERThis report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this section, we present gyrofluid models for drift wave turbulence involving impurities. They are simplified forms of the Sugama-Watanabe-Horton equations for the density, the parallel velocity and the pressure for each species (Sugama et al 2007).…”
Section: System Of Gyrofluid Equationsmentioning
confidence: 99%
“…In this section, we present gyrofluid models for drift wave turbulence involving impurities. They are simplified forms of the Sugama-Watanabe-Horton equations for the density, the parallel velocity and the pressure for each species (Sugama et al 2007).…”
Section: System Of Gyrofluid Equationsmentioning
confidence: 99%
“…These are finite electron gyro-radius fluid equations that are valid in the wavenumber range ρ [12,13] either in the adiabatic limit described by the adiabatic gas constant Γ or with Landau-fluid closure which is strongly dissipative withq (k) = χ e |k |v e n e δT e (k), where χ e is a suitable constant of order unity. Typically χ e is chosen to match the associated growth rate γ(k ⊥ , k , χ e ) with the values derived from the kinetic dispersion relation that is free of the closure problem.…”
Section: Gyrofluid Etg Modelmentioning
confidence: 99%
“…57 This model has frequently been used as a simplified description of the non-linear interchange dynamics in the SOL of magnetically confined plasmas. [58][59][60][61][62][63][64][65][66] In Ref. 57 it was found that the fluctuation time series are well described as a super-position of Lorentzian pulses, resulting in an exponential frequency power spectral density.…”
Section: Introductionmentioning
confidence: 99%